Development of a Match-Scenario Training Model for Decision Making and Mental Toughness in Sepak Takraw - Zieka Mutiara Adelita; Agus Raharjo (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aims to develop a match scenario-based mental training model (MLMBSP) to improve decision making and mental toughness of sepak takraw athletes in preparation for the 2026 Central Java PORPROV. The research employed a Research and Development (R&D) method using the 4D model (Define, Design, Develop, Disseminate). Thirty sepak takraw athletes from various regions in Central Java participated as research subjects. Research instruments included expert validation sheets, decision making questionnaires, mental toughness questionnaires, and model practicality questionnaires. Expert validation results showed average scores of 4.06 (Decision Making), 4.06 (Mental Toughness), 3.84 (DM Rubric), 4.00 (MT Rubric), 4.34 (DM Questionnaire), 4.19 (MT Questionnaire), and 4.59 (MLMBSP Model), categorized as valid to very valid. Practicality test results showed an average score of 4.44 categorized as very practical. Pre-test and post-test data demonstrated improvement in decision making from moderate (mean 3.06) to high (mean 3.99), and mental toughness from moderate (mean 2.79) to high (mean 4.20). The model comprises three main scenarios: (1) tight score 13-13, (2) comeback from deficit 5-12, and (3) facing opponent's match point, integrated with imagery and self-talk techniques. This study contributes significantly to the development of a more holistic and psychologically oriented sepak takraw athlete training model